2016
DOI: 10.1128/mbio.01254-16
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Nuclear F-Actin Induction in Human Cytomegalovirus Nuclear Egress

Abstract: Herpesviruses, which include important pathogens, remodel the host cell nucleus to facilitate infection. This remodeling includes the formation of structures called replication compartments (RCs) in which herpesviruses replicate their DNA. During infection with the betaherpesvirus, human cytomegalovirus (HCMV), viral DNA synthesis occurs at the periphery of RCs within the nuclear interior, after which assembled capsids must reach the inner nuclear membrane (INM) for translocation to the cytoplasm (nuclear egre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 49 publications
9
41
0
Order By: Relevance
“…Capsids of alphaherpesviruses move from the NRC to the nuclear rim by diffusion rather than by dependence on F actins (73)(74)(75). However, the migration of HCMV capsids is dependent on F actins (13,75). Although the two subunits of NEC are highly conserved across the Herpesviridae family (pUL50 and pUL53 of HCMV, pUL34 and pUL31 of HSV-1 and pseudorabies virus, ORF27 and ORF29 of varicella-zoster virus, and BFRF1 and BFLF2 of Epstein-Barr virus [75]), viruses egress in different ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capsids of alphaherpesviruses move from the NRC to the nuclear rim by diffusion rather than by dependence on F actins (73)(74)(75). However, the migration of HCMV capsids is dependent on F actins (13,75). Although the two subunits of NEC are highly conserved across the Herpesviridae family (pUL50 and pUL53 of HCMV, pUL34 and pUL31 of HSV-1 and pseudorabies virus, ORF27 and ORF29 of varicella-zoster virus, and BFRF1 and BFLF2 of Epstein-Barr virus [75]), viruses egress in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…HCMV capsids have a diameter of about 85 nm, which prevents their direct transport into the cytoplasm through intact nuclear pores (which have a diameter of about 39 nm) (6,(10)(11)(12). Therefore, HCMV nuclear egress occurs in several steps: (i) capsids move from NRCs toward the periphery of the nucleus via F-actin filaments (13), which may help capsids gain contact with the inner nuclear membrane (INM). (ii) Viral nuclear egress complexes (NEC), encompassing viral proteins, such as pUL50, pUL53, and RASCAL, recruit viral kinase pUL97 and cellular proteins, including p32/ gC1qR, emerin, protein kinase C, etc., to phosphorylate nuclear lamins.…”
mentioning
confidence: 99%
“…The first step, capsid movement to the nuclear periphery has recently become controversial, with some studies suggesting roles for the nuclear actomyosin system in capsid motility [16,17,22 •• ], and others not [18,19 •• ]. Additional studies are needed to rigorously test the capacity of different herpesvirus capsids to undergo directed movement in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, however, whether herpesvirus infection induces nuclear F-actin, and whether capsids undergo actin-dependent, directed movement toward the nuclear periphery have become controversial [18, 19 •• , 20, 21 22 •• ]. One report found that infections with several herpesviruses did not induce nuclear F-actin in murine fibroblasts stably expressing the actin-binding peptide, LifeAct-GFP [18].…”
Section: Capsid Movement To the Nuclear Peripherymentioning
confidence: 99%
See 1 more Smart Citation